Kajian Penggunaan Teknologi IR 4.0 Dalam Pengurusan Sisa Pepejal Bagi Kerja Pembinaan di Tapak Bina - Aminuddin, Aina Azwa; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
Previous studies shown the potential of ICT or technology that has been brought by Industrial Revolution (IR) 4.0 in order to improve waste management. The variety of technology can be taken as a study for a variety of waste management as a solution to a sustainable level. Ineffective construction waste management could bring a negative impact towards surroundings as well as human beings. Besides, construction waste management still using the conventional practices which will affect the time taken for the waste management. Two objectives had been designed which are to study the challenges towards the usage of technology IR 4.0 in a way to assist waste management in a construction site and to identify methods of improvement with the use of technology IR 4.0 in order to reduce construction waste. The research scope for this study is focusing on contractor grade G7 around Johor state. 248 respondents had been chosen through Krejcie & Morgan (1970) sampling method. Research method for this study is quantitative method through questionnaire form. Next, the Statistical Science Social Package (SPSS) had been used to analyse data. Descriptive analysis including min score was needed to determine the challenges and methods of improvement with the use of technology IR 4.0 in a way to assist waste management in a construction. Research findings shown that the challenges towards the usage of technology IR 4.0 in a way to assist waste management can be overcome with the suitable applications of methods of improvement for construction waste. In conclusion, study of utilization of technology IR 4.0 for construction waste management in a construction site can be a guideline for more effective and efficient construction waste management in the near future.